2018
DOI: 10.5194/hess-22-2187-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of actual evapotranspiration over a semiarid heterogeneous land surface by means of coupled low-resolution remote sensing data with an energy balance model: comparison to extra-large aperture scintillometer measurements

Abstract: Abstract. In semiarid areas, agricultural production is restricted by water availability; hence, efficient agricultural water management is a major issue. The design of tools providing regional estimates of evapotranspiration (ET), one of the most relevant water balance fluxes, may help the sustainable management of water resources. Remote sensing provides periodic data about actual vegetation temporal dynamics (through the normalized difference vegetation index, NDVI) and water availability under water stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 89 publications
0
22
0
1
Order By: Relevance
“…Using the two‐source energy balance model (TSEB) (Norman et al, ), some recent studies have reported RMSD to the order of 72–135 and 52–131 W m −2 in hourly λE and Η for a semi‐arid grassland in Spain (Kustas et al, ), 95–166 W m −2 in hourly λE (Song et al, ) to 45–50 W m −2 in daily λE for semi‐arid irrigated cotton in Texas and Arizona (Colaizzi et al, ; French et al, ), and 50–59 W m −2 in hourly λE for irrigated maize in China (Song et al, ). A variant of TSEB model (SPARSE model) is found to produce 43–47 W m −2 in instantaneous λE and 50–80 W m −2 in hourly λE in Tunisia and Morocco (Boulet et al, ; Saadi et al, ). Considering the error statistics of state‐of‐the‐art SEB models and their parameterization uncertainties (Timmermans et al, ); the performance of STIC1.2 indicates substantial potential of this model towards bridging thermal infrared sensing and physically‐based evapotranspiration modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Using the two‐source energy balance model (TSEB) (Norman et al, ), some recent studies have reported RMSD to the order of 72–135 and 52–131 W m −2 in hourly λE and Η for a semi‐arid grassland in Spain (Kustas et al, ), 95–166 W m −2 in hourly λE (Song et al, ) to 45–50 W m −2 in daily λE for semi‐arid irrigated cotton in Texas and Arizona (Colaizzi et al, ; French et al, ), and 50–59 W m −2 in hourly λE for irrigated maize in China (Song et al, ). A variant of TSEB model (SPARSE model) is found to produce 43–47 W m −2 in instantaneous λE and 50–80 W m −2 in hourly λE in Tunisia and Morocco (Boulet et al, ; Saadi et al, ). Considering the error statistics of state‐of‐the‐art SEB models and their parameterization uncertainties (Timmermans et al, ); the performance of STIC1.2 indicates substantial potential of this model towards bridging thermal infrared sensing and physically‐based evapotranspiration modeling.…”
Section: Discussionmentioning
confidence: 99%
“…13 Comparison of estimated evapotranspiration from the modified SW model driven by Landsat-7 and Landsat-8 and measured by the eddy covariance system (a) and the scintillometer (b) between scintillometer measurement and ET estimated using the Two-source Energy Balance model (TSEB) over an heterogeneous area covered by Millet (58%), Fallow savannah (23%) and Degraded shrubs (19%) in the region of Niamey city, Niger. In the same vein, Saadi et al (2018) have used an extra-large scintillometer to validate ET values estimated using Soil Plant Atmosphere and Remote Sensing Evapotranspiration (SPARSE) model over a landscape dominated by agriculture products (cereals, olive groves, fruit trees, market gardening). They found a RMSE and R 2 of about 0.06 mm/h and 0.55, respectively.…”
Section: Evapotranspiration Mappingmentioning
confidence: 99%
“…By contrast, the scintillometer technique that was recently developed allows for measurements of sensible (optical LAS) and latent (microwave LAS) heat fluxes over transects up to 10 km (Ezzahar and Chehbouni 2009;Ezzahar et al 2009b, a;Zieliński et al 2013Zieliński et al , 2017Yee et al 2015). In addition, scintillometers are easy to install, to monitor and can provide measurements of the surface fluxes over complex surfaces which makes them suitable for validating remote sensing-based methods (Duchemin et al 2008;Tang and Li 2015;Huang et al 2016;Ait Hssaine et al 2018;Saadi et al 2018). The LAS applies the Monin-Obukhov Similarity Theory (MOST) to estimate the sensible heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, large or extra-large scintillometers (LAS or XLAS) provide spatially averaged turbulent fluxes along transects that can reach 10 km [16][17][18][19]. Success in validating remote sensing-based ET against LAS measurements has already been demonstrated in some other areas of the world [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%